in Theory of Computation
165 views
1 vote
1 vote

14.Show that the grammar S → aSb |SS| e is ambiguous, but that the language denoted by it is not.

Can someone share the approach for second part.

in Theory of Computation
by
165 views

2 Answers

0 votes
0 votes

there is no specific approach for solving these kind of questions.

question ask that, show that there exist one unambiguous Grammar which is equivalent to the given grammar.

 

check this : 

S -> epsilon | ab | AB

B -> AB| A

A -> aAb | ab | aABb

edited by
0 votes
0 votes
S ->∈ | ab | AB

B -> AB| A

A -> aAb | ab | aABb

Related questions